IMPLEMENTATION OF GENERATIVE LEARNING MODEL TO IMPROVE STUDENT’S OF ISLAM ABHARIYAH JUNIOR HIGH SCHOOL CRITICAL THINKING SKILLS - Sri Yuliyanti; Saiful Prayogi; Bq. Azmi Sukroyanti (Universitas Pendidikan Mandalika, 2016)
This research aims to enhance students’ critical thinking skills of SMP Islam Abhariyah on the academic year 2015/2016 through the application of the generative learning model. Research method used was classroom action research (PTK). This research was conducted in two cycles. Each cycle consist of planning, implementating, observating, and reflecting. Data learning activities of the students and teachers’ activities obtained by observation, while data on students’ critical thinking skills test was obtained by an evaluation at the end of each cycle. The subject of this study was 28 students in VIII-B class. Application of the generative learning model in this study considered as successful if the value of critical thinking skills of the students at a minimum categorized as critical. The data for student’s critical thinking skills was accomplished by using an essay test, and the average value of students is 41.96 (categorized very less critical) whit classical completeness achieved only 3,57% in the cycle I and in the cycle II showed the average value of the students is 68,92 (categorized critical) whit classical completeness increased to 85,71%. Research data of student’s activities was taken by using the student’s observation sheet. The average score in the cycle I is 46.50 (categorized as fairly active) and in the cycle II is 66.00 (categorized as active). The data of teacher’s activities was taken by using teacher’s observation sheet. The presentation of learning material is 64,28% (categorized as good) in the cycle I and 91,06% (categorized as very good) in the gathering II. Thus, the conclusion to this study is the application of the generative learning model can improve students’ critical thinking skills.